2017
DOI: 10.1002/osp4.133
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with liraglutide may improve markers of CVD reflected by reduced levels of apoB

Abstract: SummaryBackgroundDislipidaemia and increased levels of apolipoprotein B (apoB) in individuals with obesity are risk factors for development of cardiovascular disease (CVD). The aim of this study was to investigate the effect of weight loss and weight maintenance with and without liraglutide treatment on plasma lipid profiles and apoB.MethodsFifty‐eight individuals with obesity (body mass index 34.5 ± 3.0 kg/m2 [mean ± SD]) were included in this study. After 8 weeks on a very low‐calorie diet (800 kcal/day), pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
2
16
1
Order By: Relevance
“…In agreement with our findings, a recent study demonstrated significant improvement in lipid and lipoprotein profiles as a result of 14 weeks treatment with liraglutide combined with modest restriction of caloric intake [28]. Reductions in apoB have also been reported in a study including obese subjects that had initially undergone a very low-calorie diet for 8 weeks followed by treatment with liraglutide in low dose (1.2 mg) for 1 year vs. meal replacements for weight maintenance [14]. Similarly, reduced apoB48 (isoform of apoB) levels were observed after a fat-rich meal in patients with type 2 diabetes treated with 1.8 mg liraglutide [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with our findings, a recent study demonstrated significant improvement in lipid and lipoprotein profiles as a result of 14 weeks treatment with liraglutide combined with modest restriction of caloric intake [28]. Reductions in apoB have also been reported in a study including obese subjects that had initially undergone a very low-calorie diet for 8 weeks followed by treatment with liraglutide in low dose (1.2 mg) for 1 year vs. meal replacements for weight maintenance [14]. Similarly, reduced apoB48 (isoform of apoB) levels were observed after a fat-rich meal in patients with type 2 diabetes treated with 1.8 mg liraglutide [29].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, LDL, HDL, IDL and VLDL particle size and content as well as circulating levels of apolipoprotein B (apo B), remnant cholesterol and fatty acids have been associated with increased risk of CVD [1013]. Recent studies in subjects treated with low dose (1.2 mg) liraglutide for 1-year for weight maintenance after a very low-calorie diet [14] or in subjects with type 2 diabetes treated with 1.8 mg liraglutide for 16 weeks and dietary counselling to achieve similar weight loss with the placebo group, reported changes in lipid profile indicative of a reduction in CVD risk [7]. However, it is unknown how early the changes in lipid profile occur with liraglutide treatment, whether they are dose-dependent and whether they are observed in patients with no overt type 2 diabetes and thus lower risk for CVD.…”
Section: Introductionmentioning
confidence: 99%
“…25 Furthermore, clinical studies have shown beneficial effects of GLP-1R agonists on cardiovascular disease markers, including atherogenic marker apolipoprotein B. 26 This study reveals a potential antiarrhythmic effect of GLP-1R activation, consistent with previously described strong cardioprotective effects of GLP-1. 2,69 One potential complication with the use of the existing drugs is that they may increase sympathetic drive, which is generally considered to be maladaptive and detrimental, contributing to the development of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 83%
“…Twice the number of patients with overweight or obesity who were randomized to liraglutide 3.0 mg in the SCALE trials achieved a mean weight loss of ≥5% of initial weight versus placebo (46–63% versus 21–27%, respectively) and improvements in weight‐related outcomes compared with placebo ( including cardiovascular outcomes, improved glycemic control, cholesterol levels, blood pressure and obstructive sleep apnea) were observed over a maximum trial period of 56 weeks 4–9 . Reduced risk of cardiovascular disease following treatment with liraglutide 1.2–1.8 mg has also been shown in other studies 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Reduced risk of cardiovascular disease following treatment with liraglutide 1.2-1.8 mg has also been shown in other studies. 10,11 Real-world evidence (RWE) is a measure of effectiveness in routine clinical practice that can complement and expand on insights from randomized clinical trials (RCTs). This evidence can be sourced from databases, patient medical chart reviews and registries.…”
mentioning
confidence: 99%